Pengaruh Brand Image, Service Quality, dan Online Customer Review Terhadap Keputusan Pembelian Produk Nivea di Batam - Tresia Putri; Suhardi Suhardi (Komunitas Dosen Indonesia, 2026)
The main objective of this research was to analyze how Brand Image, Service Quality, and Online Customer Review influence the Purchase Decision of Nivea Products in Batam City both simultaneously and partially. The number of samples tested was 204 people with a purposive sampling method. Respondents were selected based on specific criteria to ensure the relevance and accuracy of the data collected. Data were obtained by distributing questionnaires, analyzed using multiple linear regression methods and tested using the SPSS version 25 application consisting of data quality tests, classical assumption tests, influence tests, and hypothesis tests. The results of this research show that the Brand Image and Service Quality variables partially and simultaneously have a positive and significant effect on the Purchase Decision of Nivea products in Batam City, while the Online Customer Review variable has a negative insignificant effect on the Purchase Decision of Nivea products in Batam City. These findings indicate that brand perception and service performance play a crucial role in shaping consumer purchasing decisions.